Perbandingan Uji Aktivitas Antibakteri Filtrat Aquadest Umbi Bawang Suna (Allium schoenoprasum L.) Terhadap Pertumbuhan Streptococcus pneumoniae Dan Escherichia coli Dengan Metode Difusi Cakram Kirby-Bauer - Bella Chrysthya Utamy; Ni Nyoman Sri Yuliani; Dewi Klarita Furtuna (Universitas Muhammadiyah Purwokerto, 2021)
Infectious diseases are one of the most frequent diseases of major health problems, caused by bacteria are still beinga health problem in developing countries as well as in developed countries. One of the mostly occurred respiratorytract infection is pneumonia, this caused by Gram-positive bacteria Streptococcus pneumoniae. Gastrointestinaldiseases that are often caused by gram-negative bacterial infections Escherichia coli. Local plant which can be foundin Central Kalimantan are Suna onion (Allium schoenoprasum L.). Suna onion (Allium schoenoprasum L.).Researchpurposes. Research was conducted to determine the influence of the Suna’s bulb (Allium schoenoprasum L.) filtratedby aquadest with a simple filtration technique on the growth of Streptococcus pneumoniae and Escherichia usingKirby-Bauer Disk Diffusion method. Method. This type of research is true experimental design research. The designused in this study was post test-only control group design. This research uses 7 treatment groups, with concentrationsof 100%, 75%, 50%, 25%, 12.5%. Aquadest as a negative control, Erytromycin and Cifrofloxacin as positivecontrols. The method used for testing the antibacterial activity are Kirby-BaueDisk Diffusionmethod.The resultsfound that the aquadest tuber extract of onion cannot inhibit the growth of Streptococcus pneumoniae andEscherichia coli. Conclusion. Aquadest filtrate of onion tubers (Allium schoenprasum L.) cannot inhibit the growthof Streptococcus pneumoniae and Escherichia coli